Lung Screen Uptake Trial: results from a single lung cancer screening round. Issue 10 (5th August 2020) - Ruparel, Mamta; Quaife, Samantha L; Dickson, Jennifer L; Horst, Carolyn; Tisi, Sophie; Hall, Helen; Taylor, Magali; Ahmed, Asia; Shaw, Penny; Burke, Stephen; Soo, May-Jan; Nair, Arjun; et al.
Abstract : The Lung Screen Uptake Trial tested a novel invitation strategy to improve uptake and reduce socioeconomic and smoking-related inequalities in lung cancer screening (LCS) participation. It provides one of the first UK-based 'real-world' LCS cohorts. Of 2012 invited, 1058 (52.6%) attended a 'lung health check'. 768/996 (77.1%) in the present analysis underwent a low-dose CT scan. 92 (11.9%) and 33 (4.3%) participants had indeterminate pulmonary nodules requiring 3-month and 12-month surveillance, respectively; 36 lung cancers (4.7%) were diagnosed (median follow-up: 1044 days). 72.2% of lung cancers were stage I/II and 79.4% of non-small cell lung cancer had curative-intent treatment.